(untitled) (Progressive Agriculture, 2017)
Pure cultures of four different isolates were established from the infected rice sheath collected different areas of Mymensingh District on the basis of different morphological characteristics including shape, colour (upper side and reverse side), sclerotial shape, sclerotial colour and compactness. The efficacy of six plant extracts viz. Garlic (Allium sativum), Neem (Azadirachta indica), Shetodron (Leucas aspera), Mahogoni leaf (Swietenia mahagoni), Mahogoni seed(Swietenia mahagoni) and Bishkatali (Polygonum hydropiper) was investigated against different the four isolates of Rhizoctonia sp. The radial mycelial growth of the fungus from 2-7 days was significantly differed among the different treatments. At 4 day after culture colony diameter was reached maximum (4.00 cm) in PDA plates of non-treated control treatment. Average colony diameter of Rhizoctonia sp. from 2-7 days after culture ranged from 0 cm to 4.00 cm. The highest colony diameter (4.00 cm) was recorded in control at 4 days after culture. At 4 days after culture, highest percent inhibition of radial mycelial growth over contril was found for Isolate 1 by Garlic (97.50%), Neem (96.75%), and Biskatali (94.25%); for Isolate 2 by Bishkatali (93.25%); for Isolate 3 by Bishkatali (95.75%), Mahogoni seed (85.75%) and Garlic (85.00%), and for Isolate 4 by Bishkatali (95.25%) and Shetodron (89.25%). Among the plant extracts, Bishkatali was highly effective to suppress mycelial growth of all isolates of Rhizoctonia sp. Progressive Agriculture 28 (3): 190-197, 2017